2021
DOI: 10.1002/wer.1547
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal performance and characteristics of gel beads immobilized anammox bacteria under different PVA:SA ratios

Abstract: Although polyvinyl alcohol and sodium alginate gel (PVA/SA) cell immobilization technology has been successfully applied in anaerobic ammonium oxidation (anammox) processes, there is no comprehensive evaluation of the PVA:SA ratio in PVA/ SA gel beads. Therefore, to determine the optimal PVA:SA ratio, the nitrogen removal performance and structure of PVA/SA anammox gel beads under different PVA:SA ratios were studied through batch experiments. The results suggested that cell immobilization technology could sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…For this reason, studies concerning the optimization of nitrogen removal by anammox bacteria in anaerobic conditions were developed. For instance, Wang et al [ 75 ] coupled UASB with gel beads in which anammox bacteria were immobilized aiming to optimize the ratio of polyvinyl alcohol and sodium alginate (PVA/SA) gel in beads. They found that highest performance in term of specific anammox activity (0.365 g N g VSS −1 d −1 ) were achieved with PVA/SA (12%/2%) gel beads [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, studies concerning the optimization of nitrogen removal by anammox bacteria in anaerobic conditions were developed. For instance, Wang et al [ 75 ] coupled UASB with gel beads in which anammox bacteria were immobilized aiming to optimize the ratio of polyvinyl alcohol and sodium alginate (PVA/SA) gel in beads. They found that highest performance in term of specific anammox activity (0.365 g N g VSS −1 d −1 ) were achieved with PVA/SA (12%/2%) gel beads [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Wang et al [75] coupled UASB with gel beads in which anammox bacteria were immobilized aiming to optimize the ratio of polyvinyl alcohol and sodium alginate (PVA/SA) gel in beads. They found that highest performance in term of specific anammox activity (0.365 g N g VSS −1 d −1 ) were achieved with PVA/SA (12%/2%) gel beads [75]. Karasuta et al [74] evaluated the influence of HRT and pH in anammox reactors and interestingly, they concluded that the varying pH in the effluent not necessarily means a lower nitrogen removal rate while anammox performance is strictly negatively correlated with the HRT of the system.…”
Section: Target Pollutants Removalmentioning
confidence: 99%
“…The ultimate use of the gel spheres is to encapsulate microorganisms for the biological treatment of wastewater. As there is no unified evaluation standard, in order to evaluate the gel spheres quantitatively, a preliminary study was conducted by equally assigning weights to five aspects (sphericity, ,, swelling, mechanical properties, oscillatory breakage rate, ,, and mass transfer properties ,, ) on the basis of previous studies by other scholars (Table ). The orthogonal experimental design factors and scoring criteria are given in Tables and .…”
Section: Methodsmentioning
confidence: 99%
“…Recovery time prior to microbial activity has been observed with other encapsulant chemistries, such as PVA/ alginate. 25 The lack of a lag period observed with the PEG beads was likely to have been a result of the high concentration of biomass that was encapsulated. In fact, methane production from the PEG-encapsulated biomass was only observed when a minimum threshold biomass concentration was encapsulated, with no methanogenic activity observed after the polymerization process when below this threshold concentration (Fig.…”
Section: Peg Encapsulant Chemistry Biocompatibilitymentioning
confidence: 99%
“…20,21 A variety of encapsulant chemistries have been presented in the literature. [22][23][24][25][26][27] Several of these are relatively easy to make and use (e.g., alginate, polyvinyl alcohol (PVA), polyethylene glycol (PEG)), 12,19,28,29 whereas others are more challenging (e.g., core-shell structures, microparticle addition). 26,[30][31][32] In addition, some of these encapsulants may be able to last for multiple years, 33 whereas the longevity of other materials is less clear.…”
Section: Introductionmentioning
confidence: 99%